G328(P) Risk of transverse myelitis following zika virus infection. (12th March 2018) - Oligbu, G; Fallaha, M; Pay, L; Ahmed, L; Adepoju, A
Abstract : Introduction: Transverse myelitis (TM) is a neurological disorder causing acute cord injury as a result of acute inflammation, and it is often associated with infectious or autoimmune disease. 20% of all cases of TM occur in children. Since 2015, an outbreak of Zika Virus infection (ZiKV) has been reported in over 30 countries. Emerging evidence suggest ZikV causes a spectrum of neurologic diseases. However, its association with TM, especially in children, is not well described. Methods: We undertook a systematic review of the English literature published from 1947 to August 2017 to evaluate the risk factors, distribution, pathogenesis, clinical presentation, management and outcomes of TM following Zika virus infection. Data sources included MEDLINE, EMBASE, Cochrane library, and references within identified articles. We also searched the papers using the ISI web of knowledge, to identify relevant articles and conference proceedings. Results: We identified 102 potential studies, of which 9 were duplicates and 89 were excluded on the basis of title and abstracts. Of the 4 eligible studies [5–8], there were 6275 with suspected ZiKV in all age groups. 695 cases were confirmed ZiKV either by RT-PCR in plasma, CSF and urine, ELIZA or MRI while excluding other aetiologies. There were 11 (1.6%) cases of TM. Among 3 studies reporting clinical characteristics and outcome, the mean age was 23 years (Range 15–43) and 63% (n=5/8) of cases were male. 40% (n=4/10) required admission to the ITU, with no reported case fatality. Conclusions and clinical implications Complications from ZiKV, although uncommon, may be severe. With international spread, clinicians need to be aware that ZiKV may be associated with TM. As only 10% of cases were children, standardising the collection and reporting for individual cases across regions and countries would further allow meaningful analysis of the data collected, enabling monitoring of trends over time.